2021
DOI: 10.3390/ijms22095035
|View full text |Cite
|
Sign up to set email alerts
|

GnRH-Related Neurohormones in the Fruit Fly Drosophila melanogaster

Abstract: Genomic and phylogenetic analyses of various invertebrate phyla revealed the existence of genes that are evolutionarily related to the vertebrate’s decapeptide gonadotropin-releasing hormone (GnRH) and the GnRH receptor genes. Upon the characterization of these gene products, encoding peptides and putative receptors, GnRH-related peptides and their G-protein coupled receptors have been identified. These include the adipokinetic hormone (AKH) and corazonin (CRZ) in insects and their cognate receptors that pair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…During reproductive diapause, lipid accumulation and the arrest of ovarian development are two typical characteristics, and AKH signaling is responsible for mobilizing lipid metabolism during increased energy requirements. 11,13 In the current study, the functions of CsAKH and CsAKHR in reproductive diapause of C. septempunctata have been elucidated.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…During reproductive diapause, lipid accumulation and the arrest of ovarian development are two typical characteristics, and AKH signaling is responsible for mobilizing lipid metabolism during increased energy requirements. 11,13 In the current study, the functions of CsAKH and CsAKHR in reproductive diapause of C. septempunctata have been elucidated.…”
Section: Discussionmentioning
confidence: 97%
“…25,26 Functionally, AKH/AKHR signaling is involved in a variety of functions as neurohormones, neurotransmitters and neuromodulators. 13,27 In D. melanogaster, decreased AKH reduces trehalose content in hemolymph, is unable to maintain glucose homeostasis, and increases survival rates under starvation stress due to low energy metabolism. 16,28,29 In Bombyx mori, injection of AKH maturation peptide increases carbohydrate content and lipid levels in hemolymph.…”
Section: Introductionmentioning
confidence: 99%
“…Orthologous peptides of vertebrate GnRH have been identified in several bilaterian animal phyla including all deuterostomes, major lophotrochozoan phyla ( e.g. , mollusks and annelids), and ecdysozoans ( Ben-Menahem, 2021 ; Kim et al, 2023 ; Lindemans et al, 2009b , Tsai and Zhang, 2008 ; Yañez Guerra and Zandawala, 2023 ). The adipokinetic hormone (AKH) and corazonin (CRZ) neuropeptides represent the invertebrate ortholog and paralog of GnRH, respectively ( Lindemans et al, 2011 ; Tian et al, 2016 ; Yañez Guerra and Zandawala, 2023 ; Zandawala et al, 2018 ).…”
Section: Conservation Of Ancestral Peptidergic Signaling Systems In ...mentioning
confidence: 99%
“…Although the Crz peptides are structurally related to the vertebrate GnRHs (Hauser and Grimmelikhuijzen, 2014;Zandawala et al, 2015), the present study was the first to explore its putative role in ovarian development. Comparably, another GnRH-related peptide RPCH has been reported to be involved in ovarian development in several species (Zandawala et al, 2015;Zeng et al, 2016;Ben-Menahem, 2021). Interestingly, although the RPCHR has been identified from several crabs (Alexander et al, 2018;Ma et al, 2018), its paralogous sequence cannot be found in the transcriptome (Tu et al, 2021) and the genome of P. trituberculatus (NCBI database: PRJNA555262).…”
Section: B a Figurementioning
confidence: 99%
“…The [Arg 7 ]-corazonin contributes to the early release of ecdysis-triggering hormone (ETH) in the moth Manduca sexta, which initiates the ecdysis behavior (Kim et al, 2004). In the fruit flies, Crz is involved in sperm transfer (Hou et al, 2018) and fertility (Gospocic et al, 2017;Ben-Menahem, 2021), the ethanol intoxication behavior (Varga et al, 2016), and regulation of metabolism (Nassel et al, 2013). Compared with insects, the reports about Crz in crustaceans are limited.…”
Section: Introductionmentioning
confidence: 99%